Mengurai Fenomena Brand Hate terhadap Reputasi Merek Produk Israel: Sebuah Tinjauan - Dinni, Salasatri Rafaa (Universitas Batanghari Jambi, 2025)
This research reviews and synthesizes studies on brand perception, consumer behavior, and the influence of political and social factors on brand relationships, highlighting key themes such as brand resentment, boycott movements, and the role of social media. Brand resentment emerged as a significant driver of negative consumer actions towards brands perceived as not aligned with personal values, as illustrated by the Starbucks case in France, where political issues fueled consumer resentment. The boycott movement as a form of brand hatred, particularly against Israeli products, demonstrates how social media mobilizes consumer sentiment and shapes brand perception among certain demographics, such as Muslim consumers. The influence of social media influencers is also crucial, as their credibility and authenticity can significantly affect brand trust, especially in politically charged contexts. In addition, the phenomenon of consumer hostility reveals how personal and national sentiments influence cross-cultural purchasing behavior, thus complicating the consumer-brand relationship. Research on media responses to terrorism underscores the importance of ethnicity and affiliation in shaping public perceptions of brands. Overall, the findings emphasize the need for companies to strategically navigate these complex dynamics, develop strong ethical stances, and engage meaningfully with consumers on relevant issues to foster loyalty and mitigate potential backlash, ultimately enhancing corporate reputation in diverse markets.